Structural molecular details of the endocytic adaptor protein CALM upon binding with phosphatidylinositol 4,5-bisphosphate-containing model membranes - Andreas Santamaria; Daniel Pereira; Nisha Pawar; Bernard T. Kelly; Javier Carrascosa-Tejedor; Mariana Sardo; Luís Mafra; Giovanna Fragneto; David J. Owen; Ildefonso Marín-Montesinos; Eduardo Guzmán; Nathan R. Zaccai; et al. (Communications Chemistry)
Abstract Clathrin assembly lymphoid myeloid leukaemia protein (CALM) is involved in the formation of clathrin-mediated endocytic coats by virtue of binding many proteins involved in the process, including clathrin itself and AP2 cargo adaptor complex. CALM is able to specifically recognize the inner leaflet of the plasma membrane by binding the membrane’s phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2). Here, a quantitative biophysical approach —combining neutron/X-ray scattering, solid-state NMR, atomic force microscopy, and quartz crystal microbalance with dissipation monitoring—, was exploited to investigate CALM interaction with PtdIns(4,5)P2-presenting model membranes. The presented experimental data reveal CALM’s folded domain partially embeds (12% volume occupancy) within the membrane, directly coordinating a cluster of 4 to 5 PtdIns(4,5)P2 molecules via phosphate interactions. The N-terminal amphipathic helix inserts ~8 Å into the headgroup region, reducing local membrane stiffness by 36% (from 22 to 14 MPa) while increasing viscoelastic dissipation. These results establish a plausible threefold curvature-generation mechanism: PtdIns(4,5)P2 clustering, helix insertion-induced lipid compaction and global mechanical softening—collectively lowering the energy barrier for membrane deformation.